Comparing the Effectiveness of Emotionally Focused Couples Therapy (Susan Johnson Model) and Schema Therapy on Self-Esteem and Cognitive Emotion Regulation in Conflicted Couples - Nosrat Talab Haghi, Aida; Jajarmi, Mahmoud; Bakhshipour, Abolfazl (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: This study aimed to compare the effectiveness of Emotionally Focused Couples Therapy and Schema Therapy on self-esteem and cognitive emotion regulation in conflicted couples.Methodology: This research employed a quasi-experimental design with pre-test, post-test, and control group. A sample of 60 individuals (30 couples) was selected using convenience sampling and randomly divided into three groups of 10 couples each. The first experimental group received Emotionally Focused Couples Therapy, while the second experimental group received Schema Therapy. The control group received no treatment. Data were collected using the Marital Forgiveness Questionnaire and analyzed using repeated measures analysis of variance.Findings: The results indicated that both therapeutic approaches were effective in enhancing self-esteem and cognitive emotion regulation (P<0.05), though Schema Therapy showed a greater impact than Emotionally Focused Couples Therapy. A significant difference was observed between the experimental groups and the control group in terms of self-esteem and cognitive emotion regulation variables.Conclusion: Schema Therapy is more effective than Emotionally Focused Couples Therapy in increasing self-esteem and cognitive emotion regulation. These findings underscore the importance of Schema Therapy in improving marital relationships and reducing conflicts.